Regional economic integration and growth of the African Union: evidence from the Multi-dimensional Regional Integration Index - Bala, Umar; Abubakar, Muhammad Bello; Yakubu, Yahaya; Adamu, Mohammad; Allayarov, Piratdin (Universiti Putra Malaysia, 2025)
This research investigated the impact of regional trade integration (RTI), regional financial integration (RFI), and multidimensional regional integration (MDRI) on the economic growth of African Union (AU) member countries based on a panel dataset for 2010-2020. The system generalised method of moments (system-GMM) was used. The results revealed that regional trade integration exerted a positive influence, regional financial integration had no significant influence, and multidimensional regional integration had a negative impact on economic growth. Finally, from the evidence of this study, it was observed that the control variables had a stronger impact on trade performance than the regional economic integration variables. The study recommends that if the African Union countries remain committed to advancing regional integration, bolstering regional trade agreements (RTAs) and streamlining cross-border trade for the seamless movement of goods and services, the region can anticipate a tangible elevation in its trade performance.